The choice of payment method in online stores depending on demographic characteristics - Piersiala, Luiza; Kabus, Judyta (Journal of Modern Science, 2023)
ObjectivesThe subject of consideration in this article is to determine differences in the form of payment on the Internet depending on selected characteristics of respondents.Material and methodsThe main research problem in this aspect was to answer the question: What types of payment instruments are used in distance transactions depending on gender, place of residence and age? The time scope of the analysis covers the period from October 2022 to February 2023. The basic research method was the CAPI method, based on a questionnaire. In order to verify the hypotheses, statistical analyzes were carried out using the IBM SPSS Statistics 26 package. It was used to analyze basic descriptive statistics together with the Shapiro-Wilk test for normality of distributions of quantitative variables. The study involved 399 people, which is a relatively small sample, so the Mann-Whitney test was an appropriate choice. The Mann-Whitney test was used to compare two independent samples in terms of their distribution. Sample 1 was women and sample 2 was men.ResultsThe Mann-Whitney test showed that the distribution of favorite payment methods among women and men is different. This means that women and men prefer different payment methods. Both women and men prefer to pay cash for online purchases. For women, the second most popular non-cash payment method is cards, and for men - bank transfer. Other non-cash methods, such as direct debit, voucher, loyalty points or PayPal, are less popular among both groups.ConclusionsThis study contributes to existing research by offering an analysis of data on Polish consumers' payment methods. The part of the article indicates possible directions of development of the PayTech sector throughout the world and in Poland specifically.